2015
DOI: 10.5194/nhessd-3-3897-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review Article: A review and critical analysis of the efforts towards urban flood reduction in the Lagos region of Nigeria

Abstract: Abstract. Urban flooding has been and will continue to be a significant problem for many cities across the developed and developing world. Crucial to the amelioration of the effects of these floods is the need to develop a knowledge base of the magnitude and frequency of these floods. Within the area of flood research, attempts are being made to gain a better understanding of the causes, impacts and pattern of urban flooding as an aid to reducing the risks it poses. This research reviews flood risk within the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Meanwhile, it has been observed that the literature is sparse in many critical areas of flooding and FRM for Nigeria. For instance Egbenta et al [2] observed that there is a paucity of information on the effects of flood hazard on the values of properties in Nigeria while Nkwunonwo et al [7] asserted that only journalistic and non-quantitative evidence are available on some critical aspects of flooding in Nigeria. A recent review by Komolafe et al [3] highlighted the absence of the use of state of the art flood models integrating all hydrological processes for accurate prediction and mapping of flooding and its associated risks in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has been observed that the literature is sparse in many critical areas of flooding and FRM for Nigeria. For instance Egbenta et al [2] observed that there is a paucity of information on the effects of flood hazard on the values of properties in Nigeria while Nkwunonwo et al [7] asserted that only journalistic and non-quantitative evidence are available on some critical aspects of flooding in Nigeria. A recent review by Komolafe et al [3] highlighted the absence of the use of state of the art flood models integrating all hydrological processes for accurate prediction and mapping of flooding and its associated risks in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of these field data is the insufficient spatial and temporal coverage, due to a limited number of observations across the area and the lack of repetition of the data acquisition over time (Townsend & Walsh, 1998) as well as the financial cost for maintenance and data processing (Houghton-Carr, 2014). The situation is worse in developing countries where other factors, such as political and institutional instabilities occurring at national or regional level (Lins, 2008) or the dependency on international aid (Hannah et al, 2011) impede the installation and the maintenance of monitoring instruments (see, for example, Nkwunonwo, Whitworth, & Baily, 2015;Komi, Neal, Trigg, & Diekkrüger, 2017).…”
Section: Key Flood Hazard Parametersmentioning
confidence: 99%
“…In the event of crises, these agencies coordinate activities ranging from rescues and recovery to building back for victims. In the DCs, it is argued that these agencies are weak while their roles are not clearly defined (Nkwunonwo et al, 2015b). Similarly, technical capacity is insufficient.…”
Section: Institutional and Technical Capacitymentioning
confidence: 99%
“…Structural measures such as chennelisation of various canals, bridges, culverts and drainage systems to evacuate more storm water are acknowledged (Adelekan, 2015). Humanitarian aids (from for examples: Religious bodies, international communities, the United Nations, foreign agents), have been prominent all along (Nkwunonwo et al, 2015b). Local planning authorities legislate against illegal structures and enforce that more building conform to local building standards.…”
Section: Lagosmentioning
confidence: 99%
See 1 more Smart Citation